Analysis of the stator topology impact on cogging torque for surface permanent magnet motor. Issue 2 (2nd March 2015) - Petkovska, Lidija; Cvetkovski, Goga; Lefley, Paul
Abstract : Purpose: – The purpose of this paper is to investigate the impact of the stator core design for a surface permanent magnet motor (SPMM) on the cogging torque profile. The objective is to show how the cogging torque of this type of motor can be significantly reduced by implementing an original compound technique by skewing stator slots and inserting wedges in the slot openings. Design/methodology/approach: – At the beginning generic model of a SPMM is studied. By using FEA, for this idealised assembly, characteristics of cogging and electromagnetic torque are simulated and determined for one period of their change. Afterwards, actual stator design of the original SPMM is described. It is thoroughly investigated and the torque characteristics are compared with the generic ones. While the static torque is slightly decreased, the peak cogging torque is almost doubled and the curve exhibits an uneven profile. The first method for cogging torque reduction is skewing the stator stack. The second technique is to insert wedges of SMC in the slot openings. By using 2D and 2 1/2D numerical experiment cogging curves are calculated and compared. The best results are achieved by combining the two techniques. The comparative analyses of the motor models show the advantages of the proposed novel stator topology. Findings: – It is presented how the peak cogging torque can be substantially decreased due to changes in the stator topology. The constraint is to keep the same stator lamination. By skewing stator stack for one slot pitch 10° the peak cogging torque is threefold reduced. The SMC wedges in slot opening decrease the peak cogging almost four times. The novel stator topology, a combination of the former ones, leads to peak cogging of respectable 0.182 Nm, which is reduced for 7.45 times. Originality/value: – The paper presents an original compound technique for cogging torque reduction, by combining the stator stack skewing and inserting SMC wedges in the slot openings.